(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Sidorenko T. D. Didactic conditions of formations of pedagogical culture of the future music teachers. In the article the feasibility of organizing a particular activity for its efficiency and the need for certain conditions for the implementation of teaching a particular set of processes designed to – the formation of a highly qualified professional.